2017
DOI: 10.1111/jace.14862
|View full text |Cite
|
Sign up to set email alerts
|

Structure and optical properties of Er‐doped CaO‐Al2O3 (Ga2O3) glasses fabricated by aerodynamic levitation

Abstract: We fabricated a series of stable Er-doped CaO-Al 2 O 3 (Ga 2 O 3 ) glasses by aerodynamic levitation (ADL) method. Using thermal analysis, we studied the influence of composition on the thermal stability of the glasses. The results unraveled the significance of composition on the stability of glasses. Magic angle spinning nuclear magnetic resonance (MAS-NMR) and Raman spectra were used to analyze the glass microstructure. The optical and spectroscopic properties were examined by UV-Vis absorption, steady-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 34 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…It can be clearly observed that, the values of T g , T x , T c , and ΔT gradually increase and also the rate of crystallization decreases as the La 3+ ions in G(LaBGeO 5 ) are replaced by Eu 3+ ions (G(LaBGeO 5 : Eu 3+ )) and Yb 3+ , Er 3+ ions (G(LaBGeO 5 : Yb 3+ , Er 3+ )). The increase in T g , T x , T c , and ΔT values and the glass‐forming ability against crystallization can be explained by two reasons: (i) the average bond strength of the glass network increases by substituting La 3+ ions by Eu 3+ ions or Yb 3+ , Er 3+ ions, suggesting the stronger bond strength of Eu–O, Yb–O, and Er–O compared with that of La–O; (ii) mixing of several different compositions usually results in disorder degree of glass thus an increase in T x , T c , and ΔT …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be clearly observed that, the values of T g , T x , T c , and ΔT gradually increase and also the rate of crystallization decreases as the La 3+ ions in G(LaBGeO 5 ) are replaced by Eu 3+ ions (G(LaBGeO 5 : Eu 3+ )) and Yb 3+ , Er 3+ ions (G(LaBGeO 5 : Yb 3+ , Er 3+ )). The increase in T g , T x , T c , and ΔT values and the glass‐forming ability against crystallization can be explained by two reasons: (i) the average bond strength of the glass network increases by substituting La 3+ ions by Eu 3+ ions or Yb 3+ , Er 3+ ions, suggesting the stronger bond strength of Eu–O, Yb–O, and Er–O compared with that of La–O; (ii) mixing of several different compositions usually results in disorder degree of glass thus an increase in T x , T c , and ΔT …”
Section: Resultsmentioning
confidence: 99%
“…We first measured the DTA curves ( Figure 1A 13 (ii) mixing of several different compositions usually results in disorder degree of glass thus an increase in T x , T c , and DT. 21 To assess the microstructure of the G(LaBGeO 5 :Yb 3+ , Er 3+ ), GC(LaBGeO 5 :Yb 3+ , Er 3+ ), SCGC(LaBGeO 5 :Yb 3+ , Er 3+ ), and C(LaBGeO 5 :Yb 3+ , Er 3+ ), XRD and SEM were performed as shown in Figure 1B-F. The glass state of the G (LaBGeO 5 :Yb 3+ , Er 3+ ) was proved by the absence of diffraction peak in the XRD spectrum and also the smooth surface in the SEM image ( Figure 1B,C).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, academic researchers in materials science and solid-state chemistry have been synthesizing glass beads for decades using aerodynamic levitation coupled to laser heating (ADL), 8,9 in order to study the properties of melts at high temperature (e.g., by X-ray or neutron scattering) 10,11 but also as a response to the evergrowing push toward new materials discovery. 12 Indeed, this containerless method facilitates the vitrification of compositions (e.g., aluminates, [13][14][15][16][17][18][19][20] gallates, 14,[21][22][23][24] titanates, 25,26 niobates, 27,28 tungstates 29 ), which fall substantially outside the category of classically defined glass formers, due to the possibility of achieving very high melting temperatures (up to 3300 K) and fast cooling rates (∼300 K s −1 ), additionally suppressing heterogeneous crystal nucleation and avoiding potential sample-crucible reactions. These exotic compositions, both in their glassy state and after controlled crystallization, can exhibit interesting features (e.g., high refractive index and transparency, persistent luminescence, advantageous electrical and mechanical properties), which make them promising candidates for future technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…prepared Er 3+ ‐doped La 2 O 3 –Ga 2 O 3 glasses with ALT and found that the glasses showed high refractive indices, low phonon energies, good IR transparency at long wavelengths 11 . Other binary or ternary glasses prepared by ALT without network former includes CaO‐Al 2 O 3 (Ga 2 O 3 ), 12 La 2 O 3 ‐Nb 2 O 5, 13 La 2 O 3 ‐Ga 2 O 3 ‐(Nb 2 O 5 or Ta 2 O 5 ), 14 La 2 O 3 ‐Lu 2 O 3 ‐TiO 2, 15 etc 16,17 . In addition to glass, transparent ceramics can also be obtained by ALT.…”
Section: Introductionmentioning
confidence: 99%